2017
DOI: 10.1186/s12859-017-1793-7
|View full text |Cite
|
Sign up to set email alerts
|

A new and updated resource for codon usage tables

Abstract: BackgroundDue to the degeneracy of the genetic code, most amino acids can be encoded by multiple synonymous codons. Synonymous codons naturally occur with different frequencies in different organisms. The choice of codons may affect protein expression, structure, and function. Recombinant gene technologies commonly take advantage of the former effect by implementing a technique termed codon optimization, in which codons are replaced with synonymous ones in order to increase protein expression. This technique r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(181 citation statements)
references
References 65 publications
4
159
0
1
Order By: Relevance
“…Using the RefSeq database from NCBI, as tabulated in the latest release of the codon usage table database (CUTD) (Athey et al 2017), we assessed the relative proportions of the different leucine and serine codons across species. We found that global usage of CUA, UUA, and UCA (per associated amino acid) scales directly and inversely with GC content at the third position of codons (GC3) and only species with extremely high GC3 had bias against CUA, UUA, and UCA as extreme as that in the rORF-containing narnaviruses (Fig.…”
Section: Comparison Of Codon Usage Across Speciesmentioning
confidence: 99%
“…Using the RefSeq database from NCBI, as tabulated in the latest release of the codon usage table database (CUTD) (Athey et al 2017), we assessed the relative proportions of the different leucine and serine codons across species. We found that global usage of CUA, UUA, and UCA (per associated amino acid) scales directly and inversely with GC content at the third position of codons (GC3) and only species with extremely high GC3 had bias against CUA, UUA, and UCA as extreme as that in the rORF-containing narnaviruses (Fig.…”
Section: Comparison Of Codon Usage Across Speciesmentioning
confidence: 99%
“…Both factors can influence the efficiency of heterologous gene expression. We compared the GC content (of open reading frames) and codon usage of M. scalaris, Closterium peracerosum-strigosum-litorale complex, C. reinhardtii, and Arabidopsis thaliana using the Codon Usage Table Database (Athey et al 2017). This web-based tool analyzes user-defined genbank accessions.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the amino acid composition of the annotated nullpeptides, we identified the amino acids Tryptophan (W), Methionine (M) and Cysteine (C) to appear much more in nullpeptides than in non-nullomeric amino acid k-mers of the same length ( Supplementary Figure 4a ). This might be due to the importance of the M codon for translation initiation and that a single base pair change can cause W and C codons to become a TAA stop codon, the second most frequent stop codon in humans 14,15 . Similarly to nullomers, the third metric we used was the number of species in which we identified each human nullpeptide in their proteome ( Figure 5g, Supplementary Table 2 ).…”
Section: Nullpeptides Are Under Negative Selectionmentioning
confidence: 99%